Antimicrobial Activities of Synthesized Silver Nanoparticles using Ethanol and Water Extract of Mirabilis Jalapa - Frida Octavia Purnomo; Asbar Tanjung; Tunas Alam (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
The focus of this study was to compare the antimicrobial activity of silver nanoparticles (AgNPs) synthesized using ethanol extracts (AgNPE) and water extracts (AgNPA) from four o’clock flowers (Mirabilis jalapa) against Staphylococcus aureus. AgNPs were characterized by UV-Vis diffraction, FTIR, SEM, and X-rays. UV-Vis analysis showed that AgNPA has an SPR band of about 460 nm and 530 nm for AgNPE, which proves the characteristics of the absorbance area of AgNPs. SEM images of AgNPE and AgNPA show a cuboid shape with a mean diameter of 80 and 30 nm, respectively and well dispersed. The response to the presence of polysaccharide biomolecules involved in forming AgNPs was analyzed using a Fourier transform infrared spectrometer. The result was that AgNPA and AgNPE have different reducing agents. The plant extracts, AgNPE and AgNPA, were studied for their antimicrobial activity against Staphylococcus aureus. The result was that both AgNPA and AgNPE showed good activity and showed that AgNPA with less inhibition was more effective than AgNPE.